A Conceptual Synthesis of Malaysia’s Rural Transformation Programme (RTP) and Indonesia’s Dana Desa: A Narrative Review - Mohd Ali, Adi Syahid; Tuan Sembok, Tuan Muhammad Zukri; Ladiqi, Suyatno; Al-Fatih, Sholahuddin (Indonesian Journal of Legal Community Engagement, 2025)
Rural development remains central to socio-economic equity in Southeast Asia, yet governance approaches vary significantly across countries. This narrative review offers a conceptual comparison between Malaysia’s Rural Transformation Programme (RTP), characterised by centralised policy control, and Indonesia’s Dana Desa, which is rooted in fiscal decentralisation and community empowerment. While each model has strengths, neither fully addresses the complexities of diverse rural settings. Through a theory synthesis approach, the study analyses structural, institutional, and participatory differences, drawing on multi-level governance, empowerment theory, and problem-driven iterative adaptation (PDIA). Based on these insights, the paper proposes the Structured and Responsive Hybrid Governance (THBR) model, a flexible framework that integrates national policy coherence with local autonomy and adaptive feedback mechanisms. The model offers a scalable approach to rural development suited to varied institutional capacities, particularly within the ASEAN context. THBR contributes to both theoretical discourse and policy design by bridging the divide between top-down and bottom-up governance in complex rural environments.